Physical properties, characterizations & solubility study between calcium sulphate and glutamic acid, n, n-diacetic acid, tetrasodium salt - Nur Faizah, Yousof (2015)
Sulphate scale is formed due to water injection of seawater to the reservoirs and causes corrosion, equipment damage, formation damage, and flow restriction. Among various types of scale, calcium sulphate is often the predominant scale produced. Thus, Glutamic acid, N, N-diacetic acid, tetrasodium salt (GLDA) is used to study the solubility of calcium sulphate (CaSO4) in the solvent. Based on the conducted experiments, the solubility of CaSO4 in GLDA is with a mass ratio of 87:1 and a detail study are carried out to study the physical properties, characterisations, and the interaction mechanism of the solvent. GLDA is an acidic solvent with a pH of 4.11, viscosity of 11.56 mPa.s and is heavier than water as its density is 1.271 g/cm3. Besides, based on the result obtained through ICPMS, GLDA contains a high amount of sodium and potassium with 37498 ppm and 12.26 ppm respectively. In CHNS test, the highest amount of atoms is carbon atom with 17.69 w% followed by hydrogen atom with 6.52 w%. Based on the FTIR and NMR spectrum, it showed that the physical interaction hydrogen bonding occurred between GLDA and CaSO4. Therefore, Glutamic acid, N, N-diacetic acid, tetrasodium salt is a suitable solvent to investigate the solubility of calcium sulphate.